Phytochemistry and biological activities of Mesua beccariana (baill.) kosterm., Mesua ferrea L. and Mesua congestiflora - Teh, Soek Sin (2012)
Phytochemical studies carried out on Mesua beccariana, Mesua ferrea and Mesua congestiflora (Clusiaceae) resulted in the isolation of eight new compounds together with twelve known compounds. Different kinds of chromatographic techniques were utilized for the purification of these isolated compounds. The characterizations of these compounds were achieved through a variety of spectroscopic techniques such as 1D and 2D NMR, UV, IR and GC-MS. The stem bark of Mesua beccariana furnished four new compounds which are two xanthones, mesuarianone (236) and mesuasinone (237), a coumarin, beccamarin (238) and a cyclodione, mesuadione (239), along with several known compounds including two anthraquinones, 4-methoxy-1,3,5-trihydroxyanthraquinone (240) and 2,5-dihydroxy-1,3,4-trimethoxy anthraquinone (241) as well as a xanthone 6-deoxyjacareubin (116). Meanwhile, seven xanthones were isolated from the root bark of Mesua ferrea three of which are new: mesuaferrin A (242), mesuaferrin B (245) and mesuaferrin C (243). Four known compounds were identified as caloxanthone C (244), macluraxanthone (87), 1,5-dihydroxyxanthone (70) and tovopyrifolin C (246). Meanwhile, chemical investigations on Mesua congestiflora afforded a new benzophenone, congestiflorone (247) together with a known xanthone α-mangostin (106). Several triterpenoids and sterols were obtained from the three Mesua species including friedelin (183), betulinic acid (248), stigmasterol (187) and β-sitosterol (188). Structural modifications were carried out on several major compounds which were mesuarianone (236), beccamarin (238), caloxanthone C (244) and congestiflorone (247). The acetylation of mesuarianone (236) afforded both the mono and diacetate derivatives which were identified as mesuarianone acetate A (249) and mesuarianone dwiacetate B (250). However, the acetylation reactions of other major compounds only successfully yielded beccamarin acetate (251), caloxanthone C dwiacetate (252) and congestiflorone acetate (253), respectively. Preliminary screenings were carried out on the crude extracts and pure compounds towards a panel of human cancer cell lines. The human cancer cell lines tested were Raji, SNU-1,K562, LS-174T, SK-MEL-28, IMR 32, HeLa, Hep G2 and NCI-H23. The cytotoxicity of mesuaferrin A (242), macluraxanthone (87) and α-mangostin (106) were strong as they possess significant inhibitory effects against all the tested cell lines. Furthermore,mesuaferrin B (245) and caloxanthone C (244) demonstrated strong cytotoxic activity against nearly all the tested cancer cell lines. Mesuaferrin B (245) exhibited mild activity towards IMR 32 and Raji cells while caloxanthone C (244) gave mild activity against LS- 174T and SK-MEL-28 cells. The Raji, K562 and HeLa cell lines were discovered to be more vulnerable to the pure compounds. However, the SNU-1, LS-174T, SK-MEL-28,IMR 32, Hep G2 and NCI-H23 cell lines were less vulnerable to the rest of the pure compounds as their cell growth were only mildly inhibited. In addition, only the non-polar to semipolar extracts (hexane to ethyl acetate) of the three Mesua species contribute to the cytotoxic effects on the panel of human cancer cell lines. Preliminary insights towards the structure-activity relationships among a series of xanthone derivatives were studied. The substituent groups comprising diprenyls, dipyranos and prenyl pyrano of the xanthone derivatives promise the cytotoxicity towards almost all the tested cancer cell lines. Antioxidant assay were evaluated using DPPH scavenging radical assay and Folin-Ciocalteu method. The methanol extracts of Mesua beccariana and Mesua ferrea showed high antioxidant activities with low EC50 values of 12.70 and 9.77 μg/mL, respectively which are comparable to that of ascorbic acid (EC50 = 5.62 μg/mL). In contrast, only mesuaferrin A (242) and macluraxanthone (87) revealed mild scavenging potential against the DPPH radical with EC50 values of 11.72 and 11.70 μg/mL, respectively. The rest of the pure compounds possess no free radical scavenging activity. On the other hand, the methanol extracts of Mesua beccariana and Mesua ferrea exhibited high phenolic contents of 363.82 and 441.33 μg in GAE while the ethyl acetate extract of Mesua congestiflora gave a higher phenolic content compared to its methanol extract with values of 369.26 and 273.87 μg in GAE, respectively. The rest of the crude extracts contributed low to moderate phenolic content with GAE values less than 130 μg of gallic acid per mg of extract. Nitric oxide (NO) assay was another test which correlated with the antioxidant assay as the inflammation process was initiated by the invasions of free radicals. Anti-inflammatory assay screening using NO assay was only performed on the crude extracts of the three Mesua species. The hexane extract of all three Mesua species showed significant inhibitory activity of NO production with more than 70% inhibition. However, the dichloromethane and ethyl acetate extracts exhibited moderate to weak NO inhibitory effects while the methanol extracts were found to be inactive in suppressing NO production.